Coordinated expression of tristetraprolin post-transcriptionally attenuates mitogenic induction of the oncogenic Ser/Thr kinase Pim-1. - Dig B Mahat; Sarah E Brennan-Laun; Elizabeth J Fialcowitz-White; Aparna Kishor; Christina R Ross; Tatyana Pozharskaya; J David Rawn; Perry J Blackshear; Bret A Hassel; Gerald M Wilson (PLoS ONE, 2012)
The serine/threonine kinase Pim-1 directs selected signaling events that promote cell growth and survival and is overexpressed in diverse human cancers. Pim-1 expression is tightly controlled through multiple mechanisms, including regulation of mRNA turnover. In several cultured cell models, mitogenic stimulation rapidly induced and stabilized PIM1 mRNA, however, vigorous destabilization 4-6 hours later helped restore basal expression levels. Acceleration of PIM1 mRNA turnover coincided with accumulation of tristetraprolin (TTP), an mRNA-destabilizing protein that targets transcripts containing AU-rich elements. TTP binds PIM1 mRNA in cells, and suppresses its expression by accelerating mRNA decay. Reporter mRNA decay assays localized the TTP-regulated mRNA decay element to a discrete AU-rich sequence in the distal 3'-untranslated region that binds TTP. These data suggest that coordinated stimulation of TTP and PIM1 expression limits the magnitude and duration of PIM1 mRNA accumulation by accelerating its degradation as TTP protein levels increase. Consistent with this model, PIM1 and TTP mRNA levels were well correlated across selected human tissue panels, and PIM1 mRNA was induced to significantly higher levels in mitogen-stimulated fibroblasts from TTP-deficient mice. Together, these data support a model whereby induction of TTP mediates a negative feedback circuit to limit expression of selected mitogen-activated genes.